2022
DOI: 10.14569/ijacsa.2022.0130174
|View full text |Cite
|
Sign up to set email alerts
|

An Early Intervention Technique for At-Risk Prediction of Higher Education Students in Cloud-based Virtual Learning Environment using Classification Algorithms during COVID-19

Abstract: Higher Education is considered vital for societal development. It leads to many benefits including a prosperous career and financial security. Virtual learning through cloud platforms has become fashionable as it is expediency and flexible to students. New student learning models and prediction outcomes can be developed by using these platforms. The appliance of machine learning techniques in identifying students at-risk is a challenging and concerning factor in virtual learning environment. When there are few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This study compares the results among classical machine learning algorithms and the proposed model gives 70-75% accuracy. Rose et al, [20] suggested a model to predict at-risk students in the early stage of the course in a cloud virtual learning environment. The dataset contains 530 records with 46 features, including student demographic details, academic progress, learning style, and other online usage information.…”
Section: Related Work 21 Classical Machine Learningmentioning
confidence: 99%
“…This study compares the results among classical machine learning algorithms and the proposed model gives 70-75% accuracy. Rose et al, [20] suggested a model to predict at-risk students in the early stage of the course in a cloud virtual learning environment. The dataset contains 530 records with 46 features, including student demographic details, academic progress, learning style, and other online usage information.…”
Section: Related Work 21 Classical Machine Learningmentioning
confidence: 99%